Socioeconomic and nutritional factors associated with age of eruption of third molar tooth among Ugandan adolescents - Kutesa, Annet Mutebi (J Forensic Dent Sci, 2019)
This study aimed to establish the influence of socioeconomic and nutritional factors on the age of eruption of the mandibular third molar among Ugandans aged 10–20 years. MATERIALS AND METHODS: This was a cross-sectional study carried out in a dental clinic of Mulago Hospital between January and December 2017. The background information was obtained from the participants using a questionnaire in the form of an oral interview. The anthropometric measurements were obtained using a tape measure and a weighing scale, while dental radiographs were used to determine the eruption stages of the mandibular third molar. STATISTICAL ANALYSIS: The data were analyzed using STATA 13 and summarized using descriptive statistics and multivariate analyses. Statistical significance was inferred at P < 0.05. RESULTS: Participants in the overweight body mass index category were statistically significantly associated with the age of the mandibular third molar eruption (P < 0.05) compared to their normal counterparts. There was no statistically significant association between socioeconomic status and age of eruption of third molar teeth (P > 0.05). Age of eruption was statistically significantly higher among males than females (P > 0.05). CONCLUSION: The findings of the present study reveal that overweight influences early eruption of the mandibular third molar tooth, although there is no trend between socioeconomic status and the age of eruption of the mandibular third molar.